Cost-Effectiveness of Hypochlorous Acid Preserved Wound Cleanser versus Saline Irrigation in Conjunction with Ultrasonic Debridement for Complex Wounds - Peter J. Mallow; John M. Hiebert; Martin C. Robson (Journal of Health Economics and Outcomes Research)
**Objective:** Low-frequency ultrasound debridement with irrigation is an effective method of wound bed preparation. A recent clinical study compared hypochlorous acid preserved wound cleanser (HAPWOC) to saline and found HAPWOC to be a more effective adjunct to low frequency ultrasound debridement. However, HAPWOC has an added cost. The primary objective of this study was to assess the cost-effectiveness of HAPWOC as an irrigation modality with low-frequency ultrasound debridement for the treatment of severely complex wounds that were destined to be closed primarily via a flap. The secondary objective of this study was to estimate the number needed to treat (NNT) to avoid a wound-related complication and its expected cost per NNT.